Thornhedge - Kingfisher, T. (Tor, Tor Publishing Group, 2023)
"There's a princess trapped in a tower. This isn't her story. Meet Toadling. On the day of her birth, she was stolen from her family by the fairies, but she grew up safe and loved in the warm waters of faerieland. Once an adult though, the fae ask a favor of Toadling: return to the human world and offer a blessing of protection to a newborn child. Simple, right? But nothing with fairies is ever simple. Centuries later, a knight approaches a towering wall of brambles, where the thorns are as thick as your arm and as sharp as swords. He's heard there's a curse here that needs breaking, but it's a curse Toadling will do anything to uphold ..."--